Mediation Role of Workplace Spirituality on Work Stress and Employee Mental Well-being: A Study on health workers - Khan, Ryan (Li Falah: Journal of Islamic Economics and Business, 2022)
This study investigates Work Stress's direct and indirect effects on Employee Mental well-being. This study uses quantitative analysis from an online questionnaire of up to 127 respondents as a research tool. The sampling technique used was the purposive sampling technique. After the data is collected, the reliability of the data is tested using validity and reliability tests. In addition, hypothesis testing using SEM-PLS. The results showed that Work Stress could reduce Employee Mental Well-being. Also, simultaneously, Workplace Spirituality can affect Employee Mental Well-being. In addition, the role of Spirituality in the Workplace as a Moderator between Work Stress and Employee Mental Health.